The relationship of teacher ratings of executive functions to emergent literacy in Head Start - Hooper, Stephen R.; Costa, Lara-Jeane C.; Green, Melissa B.; Catlett, Stephanie R.; Barker, Alexandra; Fernandez, Edmund; Faldowski, Richard A. (Reading & writing, 2020)
The purpose of this study was to investigate the concurrent relationships between selected teacher-rated executive function (EF) and a comprehensive array of emergent literacy skills in preschool children after adjusting for targeted covariates including at-risk status. The sample comprised 114 three-year-olds who were attending Head Start preschool. The teacher-completed Behavior Rating Inventory of Executive Function-Preschool was used to generate three predictor variables: Inhibitory Self-Control, Flexibility, and Emergent Metacognition. The emergent literacy outcomes included the Teacher Ratings of Oral Language and Literacy Reading, Writing, and Language scales, Stanford Binet Intelligence Scale 5 Vocabulary Subtest, Test of Early Reading-3 Convention Subtest, and Print Knowledge and Phonological Awareness subtests from the Test of Preschool Early Literacy. Findings revealed that after controlling for selected covariates (age, gender, classroom) and at-risk status, when the three EF indices were included in the model the amount of variance significantly increased for all of the emergent literacy outcomes, with the total variance accounted for ranging from 32% (Phonological Awareness) to 59% (pre-Writing). Emergent Metacognition was a significant predictor for nearly every outcome except Phonological Awareness and Reading Conventions; Flexibility and Inhibitory Self-Control were significant predictors of Language. Significant interactions were present for at-risk status and teacher ratings of both Flexibility and Inhibitory on TERA-3 Conventions, but these findings appeared to be affected more by the not at-risk group than the at-risk group. Results reinforce the potential added importance of teacher ratings of EF, particularly with respect to the integrity of early developing EF, in the prediction of emergent literacy skills in young preschool children.